Identification and utilization of a new Bacillus amyloliquefaciens XY-1 against Fusarium head blight - Xu, Xiao; Cheng, Yifan; Fang, Zhengwu; Yin, Junliang; Shen, Huiquan; Ma, Dongfang (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB) is a global wheat grain disease caused by Fusarium graminearum. Biological control of FHB is considered to be an alternative disease management strategy that is environmentally benign, durable, and compatible with other control measures. In this study, to screen antagonistic bacteria with the potential to against FHB, 45 strains were isolated from different tissues of wheat. Among them, seven strains appeared to effectively inhibit F. graminearum growth, the antagonistic bacterium named XY-1 showed a highly antagonistic effect against FHB using dual culture assays. The strain XY-1 was identified as Bacillus amyloliquefaciens by 16S rDNA sequence. Antibiotic tolerance of antagonistic bacteria showed that XY-1 had antagonistic activity against Colletotrichum gloeosporioides, Rhizoctonia solani, Sclerotium rolfsii, and Alternaria alternata. Nutrition tests showed that the most suitable carbon and nitrogen sources were glucose and beef extract, respectively. The optimum growth temperature and pH value were 28 ℃ and 7.4. Antibiotics tolerance cultivation showed that XY-1 had strong resistance to Chloramphenicol and Ampicillin. Wheat spikes inoculation antagonism tests showed that strain XY-1 displayed strong antifungal activity against F. graminearum. Our study laid a theoretical foundation for the application of strain XY-1 as a biological agent in the field to control FHB.